Study of kefiran production from cheese whey - D'Ascensão, João Diogo Mendes (2022)
Cheese whey is the main by-product of dairy industries, which is massively produced worldwide. Its disposal may represent a serious environmental issue due to its high organic content, therefore, it is of interest to find more solutions for its valorisation. An interesting approach is the conversion of its lactose into value-added products through microbial fermentation. Kefiran is an exopolysaccharide with approximately equal amounts of D-glucose and Dgalactose, whose remarkable properties make it possible to be of use in a wide range of applications in the medicine, pharmaceutical and food industries. This polymer can be produced during fermentation, with the use of kefir grains, a complex microbial community embedded within a kefiran matrix, containing several species of lactic acid bacteria (LAB), acetic acid bacteria (AAB) and yeasts, living in symbiose. Nevertheless, the bacterium Lactobacillus kefiranofaciens is considered to be the main responsible for kefiran production. The objective of this work was the study of kefiran production, by kefir grains, in cow’s cheese whey (CWC), diluted cow’s cheese whey (CWCD), sheep’s cheese whey (CWS) and in synthetic medium (MRSL broth). In this study, fermentations in batch and fed-batch mode were performed. Initially, MRSL broth medium was used to optimise the process. A fermentation time of 100 h was found to be optimal, since it led to the highest kefiran productivity value. The ideal stirring speed was concluded to be 80 rpm, as it provided the best balance between kefiran production and kefir grains’ conservation. Relatively to the optimal initial lactose concentration, results were dependant on the stirring speed, with no noticeable inhibition by substrate occurring. The best results in terms of kefiran concentration, 1.640 g/L, and productivity, 0.390 g/L.day, were both reached after 100 h of fermentation, using a MRSL broth medium containing 40 g/L of lactose, at 160 rpm. Regarding cheese whey, kefiran production values were promising. The highest concentration of kefiran, 1.190 g/L, was attained in the fed-batch fermentation of the cheese whey sample CWC, which lasted for 510 h, at 80 rpm, while the highest kefiran productivity value, 0.224 g/L.day, was achieved in the batch fermentation of the cheese whey sample CWCD, after 50 h, at 80 rpm. When characterising the kefiran samples produced with the different media, an acid hydrolysis confirmed a glucose to galactose ratio of approximately 1:1 and, together with the analysis by Fourier-transform infrared (FTIR) spectroscopy, also confirmed that kefiran was successfully produced in this study. Additionally, the analysis by scanning electron microscopy (SEM) revealed a foam-like structure with a high porosity level, which is a very desirable characteristic for the production of kefiran scaffolds. This study showed that it is possible to produce kefiran with the use of a lowcost carbon source, such as cheese whey, with fairly solid results, even though the process scale-up still needs to be addressed to enable an eventual industrial implementation.